Battling PFAS: Microbial frontlines and removal mechanisms in constructed wetlands - Yaoxuan Cheng; Jiacheng Shang; Xuanrui Liu; Zeming Shi; Xinyue Zhao; Lixin Li (Journal of Environmental Chemical Engineering, 2026)

LncRNA TUG1 promotes hypertrophic scar formation via the miR-627/IGF1R axis - Zeming Bai; Ziyang Han; Xiangzi Kong; Rirui Zhao; Haiwei Sun; Hai Huang; GuYue Wang; Zhe Li; Kai Tao; Jiulong Liang (Journal of Molecular Histology, 2026)
Hypertrophic scars (HS) are fibrotic skin disorders driven by abnormal fibroblast activity. The molecular mechanisms underlying HS remain incompletely understood, particularly the role of non-coding RNAs. Expression levels of lncRNA TUG1, miR-627, and IGF1R were measured in HS tissues and fibroblasts using qRT-PCR and Western blotting. Dual-luciferase assays validated direct interactions. Functional effects of TUG1 and miR-627 on fibroblast proliferation and migration were assessed using MTT and Transwell assays. A rabbit ear model of HS was used to examine in vivo effects of TUG1 and miR-627 modulation on scar formation and molecular expression. TUG1 was significantly upregulated in HS tissues and inversely correlated with miR-627, which was downregulated. TUG1 promoted fibroblast proliferation and migration by directly sponging miR-627, thereby lifting repression on IGF1R, a known pro-fibrotic effector. Luciferase assays confirmed direct binding of miR-627 to both TUG1 and IGF1R. Co-transfection of miR-627 attenuated TUG1-induced IGF1R upregulation and reversed its pro-fibrotic cellular effects. In vivo, TUG1 overexpression led to increased scar thickness, collagen deposition, and IGF1R expression, while miR-627 overexpression mitigated these effects. Co-administration of both restored scar morphology and molecular markers to near-control levels. TUG1 promotes hypertrophic scar formation by sponging miR-627 and derepressing IGF1R. This newly identified TUG1–miR-627–IGF1R axis plays a central role in HS pathogenesis and may serve as a promising therapeutic target for fibrotic skin disease.

Dynamic mesh-based investigation of thermal environment during mars ascent vehicle launch phase - Zhongyi Sun; Zhanxun Che; Chengeng Zhao; Zeming Wang; Guigao Le (Advances in Space Research, 2026)

Customizable sub-nanometer vertical-step grayscale lithography - Haonan Ma; Shijie Zhao; Xia Liu; Ziying Hu; Xu Han; Hongtao Li; Zeming Jin; Mingdi Zhang; Jixiang Li; Wenke Fu; Yunyun Dai; Yuan Huang; et al. (Science Bulletin, 2026)

Cohydrothermal carbonization of cellulose and organic matter from municipal sewage sludge for the controllable synthesis of N-doped porous carbon for supercapacitor electrodes - Linxin Yin; Chang Liu; Yulu Yang; Zihan Du; Guanzhong Mu; Zeming Zhao; Changqing Cao; Pei-Gao Duan; Krzysztof Kapusta (Journal of Environmental Management, 2026)

Non-directly bonded single-atom pairs towards H2/CO electrooxidation - Tongtong Yang; Heng Liu; Hengjie Liu; Weiyi Zhao; Jiawei Ge; Wenhui Wang; Shuai Yang; Meijian Tang; Kai Wei; Kangcheng Wang; Zeming Qi; Xian Wang; et al. (Science Bulletin, 2026)

Feedstock loading and pressure synergy in high-solid microalgae HTL: Boosting bio-oil yield while reducing nitrogen content - Zhicong Wang; Zeming Zhao; Collins Chimezie Elendu; Peigao Duan (Biomass and Bioenergy, 2026)

Geochemical signature and genesis of heavy metals in soils and sediments from a typical pyrite mining area in Southwestern China - Kai Zhao; Zeming Shi; Yinghai Zhu; Yixin Li; Qi Liu; Qiuyu Huang; Xiaohan Liu (Environmental Geochemistry and Health, 2026)

Identification of Mitochondrial and Succinylation Modification-Related Gene Signature in Ischemic Stroke - Lixia Wang; Jishuai Zhao; Hui Cai; Xiaoling Ying; Yonglei Liu; Zeming Luo; Heyan Chen; Lin Yang (Molecular Neurobiology, 2025)

China’s practice from coastline management towards sea-land integration - Qiwei Zhao; Xin Teng; Xue Meng; Zeming Du; Panpan Zhang; Wanchao Kang (Frontiers in Marine Science, 2025)
Integrated Sea-land management is an important feature of ecosystem-based management, and it is also the trend of marine spatial planning. China is one of the first countries worldwide to implement marine spatial planning which is mainly expressed as marine functional zoning (MFZ), and it has established a coastline management system for the connection between marine management and land management. In this paper, 18 national and local coastline management policies in China are analyzed. It is concluded that coastline management ensures the formulation, implementation, evaluation, and revision of MFZ, promotes the extension of MFZ to land, gradually evolves into coastal zone planning based on coordinated land and marine development, and promotes sea-land integration management in China. Taking Tangshan City in Hebei Province as an example, it is further proven that at the local level, coastline management accelerates the progress of sea-land integration.

Causes and influencing mechanisms of differences in phosphorus occurrence forms in sediments of different types of urban lakes - Yinghai Zhu; Zeming Shi; Qian Li; Chengjie Zou; Na Zhang; Xinyu Wang; Kai Zhao (Science of The Total Environment, 2025)

Seasonal and spatial variations of nutrients and environmental effects under anthropogenic influence in Daya Bay, China - Jincheng Zhao; Jiawei He; Cai Li; Zeming Yang; Cong Liu; Xianqing Zhang; Min Qin; Dejing Tang; Wen Zhou; Zhantang Xu; Yuanyue Cheng (Frontiers in Marine Science, 2025)
Nutrients are crucial factors for the growth of phytoplankton, and their biogeochemical processes directly impact marine biodiversity. In this study, based on two cruise observations in spring and summer of 2024, the seasonal and spatial variations of nutrients, chlorophyll a, and other ecological indicators in Daya Bay were explored. The results indicated that the average concentrations of dissolved inorganic nitrogen and silicate were 3.61 ± 3.99 µM and 26.27 ± 13.91 µM in summer, respectively, compared with 2.48 ± 1.53 µM and 23.8 ± 6.77 µM in spring. The average concentration of dissolved inorganic phosphate was 0.29 ± 0.12 µM in summer, lower than 0.32 ± 0.09 µM in spring. The stoichiometric proportion among nutrients at most monitoring stations were far from Redfield ratio, and a succession from N-limited to P-limited was observed. A transformation has been observed in the dominant composition of dissolved inorganic nitrogen, shifting from ammonia to total oxidized nitrogen as the main component, which is mainly attributable to the decrease in aquaculture activities in Daya Bay over the last 3 years. In addition, the warm wastewater discharge from nuclear power stations directly influences the distribution of phytoplankton in the surrounding areas. This study provides timely information regarding recent shifts in ecological indicators and is significant to the ecological protection, environmental management, and policy adjustment in Daya Bay.

Enhancing hydrogen storage performance by N-doping induced chemical and structural effects in porous carbon materials - Zeming Zhong; Xue Gao; Liangjun Huang; Hui Wang; Yujun Zhao; Min Zhu (Chemical Engineering Journal, 2025)

Single-cell atlas profiling revealed cellular characteristics and dynamic changes after PD-1 blockade therapy of brain metastases from laryngeal squamous cell carcinoma - Yunzhi Zou; Hao Duan; Zekun Deng; Rong Xiang; Jixiang Zhao; Zhenhua Zhang; Wanming Hu; Yuanzhong Yang; Zeming Yan; Shujuan Wen; Zexian Liu; Gao Zhang; et al. (Molecular and Cellular Biochemistry, 2025)
Brain metastasis (BM) in laryngeal squamous cell carcinoma (LSCC) is uncommon but prognosis is poor. Anti-PD-1 immunotherapy benefits some advanced LSCC cases, yet its efficiency is limited by tumor complexity. We analyzed paired metastatic tumor samples from before and after immunotherapy using single-cell RNA sequencing (scRNA-seq), along with a primary LSCC dataset and bulk RNA sequencing. This identified changes post-immunotherapy and revealed differences in single-cell transcriptomes among LSCC, primBM, and neoBM. Our findings show that anti-PD-1 treatment suppresses metastasis-promoting pathways like VEGF and EMT in cancer cells, and alters immune cell functions. Notably, it upregulates T cell activation, leading to CD8 T cell exhaustion from excess heat shock proteins, notably HSPA8. However, CD8 T cell cytotoxic functions improve post-treatment. In myeloid cells, anti-PD-1 therapy enhances antigen presentation and promotes a proinflammatory shift post-metastasis. Additionally, NUPR1 is linked to BM in LSCC, and NEAT1 is a potential metastatic cancer cell cycle participant. Our study provides insights into cancer heterogeneity and the impact of PD-1 immunotherapy on metastasis, aiding precise diagnosis and prognosis.

Machine learning-based surrogate models for fast impact assessment of a new building on urban local microclimate at design stage - Zeming Zhao; Hangxin Li; Shengwei Wang (Building and Environment, 2024)

A microfluidic analyzer based on liquid waveguide capillary cells for the high-sensitivity determination of phosphate in seawater and its applications - Jincheng Zhao; Zeming Yang; Dejing Tang; Min Qin; Wen Zhou; Cong Liu; Zhantang Xu; Yuanyue Cheng; Xianqing Zhang; Cai Li (Analytica Chimica Acta, 2024)

Mining subsidence monitoring using distributed scatterers InSAR based on Goldstein filter and Fisher information matrix-weighted optimization - Zeming Tian; Lifeng Zhao; Hongdong Fan; Tao Lin; Tao Li (Natural Hazards, 2024)

Chain-mediating effect of interaction between telomeres and mitochondria under oxidative stress in coke oven workers - Zhiguang Gu; Zeming Niu; Zhaofan Yan; Yahui Fan; Jing Sun; Xiangkai Zhao; Xiaoran Duan; Wu Yao; Yongli Yang; Wei Wang (Environmental Pollution, 2023)

Implanting nitrogen-doped graphene quantum dots on porous ultrathin carbon nitride for efficient metal-free photocatalytic hydrogen evolution - Hanxiang Chen; Zhao Mo; Zeming Wang; Pengcheng Yan; Peipei Sun; Guanyu Wu; Jinyuan Zhang; Xianglin Zhu; Liang Wang; Hui Xu (Journal of Environmental Chemical Engineering, 2023)

Impact of meteorological conditions at multiple scales on ozone concentration in the Yangtze River Delta - Zezheng Zhao; Zeming Zhou; Ana Russo; Huadong Du; Jie Xiang; Jiping Zhang; Chengjun Zhou (Environmental Science and Pollution Research, 2021)

Crystal structure of norsethite-type BaMn(CO3)2 and its pressure-induced transition investigated by Raman spectroscopy - Wen Liang; Lin Li; Yuan Yin; Rui Li; Zeming Li; Xiqiang Liu; Chaoshuai Zhao; Shuguang Yang; Yong Meng; Zengsheng Li; Yu He; Heping Li (Physics and Chemistry of Minerals, 2019)

Metamorphic P-T-t Path of UHT Granulites from the North Tongbai Orogen, Central China - Hua Xiang; Zeming Zhang; Liming Zhao; Zengqiu Zhong; Hanwen Zhou (Journal of Earth Science, 2018)

Correlation Between Iodine Intake and Thyroid Disorders: A Cross-Sectional Study from the South of China - Hengqiang Zhao; Yuan Tian; Zeming Liu; Xiaoyu Li; Mengyu Feng; Tao Huang (Biological Trace Element Research, 2014)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Metabolic profiling based on LC/MS to evaluate unintended effects of transgenic rice with cry1Ac and sck genes - Yuwei Chang; Chunxia Zhao; Zhen Zhu; Zeming Wu; Jia Zhou; Yanni Zhao; Xin Lu; Guowang Xu (Plant Molecular Biology, 2012)